2015
DOI: 10.1111/tpj.12744
|View full text |Cite
|
Sign up to set email alerts
|

THB1, a truncated hemoglobin, modulates nitric oxide levels and nitrate reductase activity

Abstract: These authors contributed equally to this work. SUMMARYHemoglobins are ubiquitous proteins that sense, store and transport oxygen, but the physiological processes in which they are implicated is currently expanding. Recent examples of previously unknown hemoglobin functions, which include scavenging of the signaling molecule nitric oxide (NO), illustrate how the implication of hemoglobins in different cell signaling processes is only starting to be unraveled. The extent and diversity of the hemoglobin protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 69 publications
2
97
0
Order By: Relevance
“…The top 10 most highly expressed or repressed genes were related to nitrogen-scavenging or photosynthesis (Table S3). For instance, THB1, a truncated hemoglobin highly expressed in the presence of nitric oxide37, was repressed by almost 300-fold. Likewise, three subunits of the urea active transporter were upregulated between 52- and 72-fold, representing one of the many enzymes whose expression are known to increase to harvest nitrogen from nitrogen-containing compounds such as ammonium, nitrate, nitrite, urea, purines, pyrimidines and amino acids38.…”
Section: Resultsmentioning
confidence: 99%
“…The top 10 most highly expressed or repressed genes were related to nitrogen-scavenging or photosynthesis (Table S3). For instance, THB1, a truncated hemoglobin highly expressed in the presence of nitric oxide37, was repressed by almost 300-fold. Likewise, three subunits of the urea active transporter were upregulated between 52- and 72-fold, representing one of the many enzymes whose expression are known to increase to harvest nitrogen from nitrogen-containing compounds such as ammonium, nitrate, nitrite, urea, purines, pyrimidines and amino acids38.…”
Section: Resultsmentioning
confidence: 99%
“…As shown herein, both are needed to synthesize NO from nitrite in vivo , so that the deficient functionality of either NR or ARC would lead to the derepression of the system, which tries to compensate the decreased NO levels. It has been previously shown that high NO leads in Chlamydomonas to repression of nitrate assimilation related genes ( NIA1 , NRT2.1, or THB2 ) (de Montaigu et al ; Sanz‐Luque et al ). Thus ARC expression seems to be also negatively regulated by NO, because the lack of NO production causes ARC derepression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…), and second, promoting reduction of THB1 for NO conversion to nitrate. THB1 is a truncated haemoglobin, which has NO‐dioxygenase activity, when reduced, and NR seems to mediate also this reduction (Sanz‐Luque et al ). In this way, by distributing electrons to ARC and THB1, NR would be playing a central role in the control of NO amounts in the cell for signalling of numerous processes.…”
Section: Discussionmentioning
confidence: 99%
“…However with the current data, we cannot discriminate which ones of these alternatives would be the correct one. Interestingly, crARC seems to have basic amino acids in the entire outer part where the Mo Cofactor is bound, and it has been described that there are mostly acid amino acids in the outside of crCitb5-1 and crCitb5-R [35], so this would explain in part the interaction between these three proteins.…”
Section: Discussionmentioning
confidence: 99%